2020
DOI: 10.1177/2054358120918457
|View full text |Cite
|
Sign up to set email alerts
|

Canadian Society of Transplantation and Canadian Society of Nephrology Commentary on the 2017 KDIGO Clinical Practice Guideline on the Evaluation and Care of Living Kidney Donors

Abstract: Purpose of review: To review an international guideline on the evaluation and care of living kidney donors and provide a commentary on the applicability of the recommendations to the Canadian donor population. Sources of information: We reviewed the 2017 Kidney Disease: Improving Global Outcomes (KDIGO) Clinical Practice Guideline on the Evaluation and Care of Living Kidney Donors and compared this guideline to the Canadian 2014 Kidney Paired Donation (KPD) Protocol for Participating Donors. Methods: A working… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
16
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(17 citation statements)
references
References 100 publications
0
16
1
Order By: Relevance
“…Four guidelines and two consensus statements recommended enquiring into previous pregnancy complications during the assessment of a potential LKD 31,32,35,40,41 . Six guidelines recommended informing the potential LKD of the increased risk of post‐donation pregnancy complications 31,33‐37 .…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Four guidelines and two consensus statements recommended enquiring into previous pregnancy complications during the assessment of a potential LKD 31,32,35,40,41 . Six guidelines recommended informing the potential LKD of the increased risk of post‐donation pregnancy complications 31,33‐37 .…”
Section: Resultsmentioning
confidence: 99%
“…Six guidelines recommended informing the potential LKD of the increased risk of post‐donation pregnancy complications 31,33‐37 . One consensus statement suggested that alternative donors should be sought for women who had not completed their family and had a history of pre‐eclampsia 40 . The 2017 KDIGO guidelines advised against excluding women solely on their desire to conceive post‐donation and suggested that women with a history of pre‐eclampsia may be suitable donor candidates 35 .…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations